2014
DOI: 10.1002/cphc.201402338
|View full text |Cite
|
Sign up to set email alerts
|

Invoking Pairwise Interactions in Water‐Promoted Diels–Alder Reactions by using Ionic Liquids as Cosolvents

Abstract: Rate constants and derived activation parameters of organic reactions in aqueous media, in particular Diels-Alder reactions, are sensitive to the presence of cosolvents in water. To enhance the solubility window of water, we introduced ionic liquids as cosolvents in the aqueous Diels-Alder reaction between anthracene-9-carbinol and N-ethylmaleimide. The reactive potentials of the organic compounds are parameterized by using semi-empirical quantum chemical methods. The principle of Savage-Wood additivity of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 136 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…41 Physicochemical properties of ionic liquids change in the presence of impurities like water, organic solvents and halide ions. [42][43][44] Therefore, prior to conning IL into the mesoporous MCM-41 support, IL as well as IL containing MCM-41 mesoporous materials were dried at 100 C under vacuum (10 À3 torr). Fig.…”
Section: Dscmentioning
confidence: 99%
“…41 Physicochemical properties of ionic liquids change in the presence of impurities like water, organic solvents and halide ions. [42][43][44] Therefore, prior to conning IL into the mesoporous MCM-41 support, IL as well as IL containing MCM-41 mesoporous materials were dried at 100 C under vacuum (10 À3 torr). Fig.…”
Section: Dscmentioning
confidence: 99%
“…The effect of decreasing viscosity on reactivity was nicely demonstrated by the observed increase in the rates of Diels-Alder reactions as a result of decreasing the viscosity of the medium, both for pure ILs and their aqueous solutions. 23,24 The use of aqueous ILs for pulp fractionation, ber spinning, 25 and as additives for improving dying of natural and synthetic bers 26 are interesting examples of the potential applications of green chemistry to improve these important industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to single out the effect of pairwise interactions between ILs and reactants on the rate of the process, 91 the same authors devised a model relating the ratios of reactivity measured in purely aqueous media and in dilute aqueous solutions of ILs, with the magnitude of these pairwise interactions. It is shown that in the presence of some ILs, reactivity is explained in terms of pairwise interactions, whereas others interact through bulk interactions.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%